Positive effects of platelet-rich plasma (PRP) and a Sanguisorba officinalis polysaccharide on the proliferation and differentiation of anterior cruciate ligament (ACL) fibroblasts in vitro - Hong Zheng; Wenya Huang; Bing He; Hongchang Tan; Pingzhi Lin; Zhengang Zha (Taylor & Francis Group, 2020)
Context Sanguisorba officinalis L. (Rosaceae), a famous traditional Chinese medicine. It was recently reported that its polysaccharide could facilitate collagen production. Objectives We investigated the mechanism by which S. officinalis polysaccharide (SOWPa) and/or platelet-rich plasma (PRP) promote regenerative potential of anterior cruciate ligament (ACL) in vitro. Materials and methods ACL fibroblasts were treated with SOWPa (25 and 100 mg/kg), PRP, PRP + SOWPa (25 and 100 mg/kg) or vehicle alone for 24, 48, or 72 h. Cell viability, migration ability and apoptosis were evaluated by MTT, transwell and flow cytometry, respectively. Western blot analysis was performed to assess associated protein expression. Results PRP, SOWPa (100 mg/kg) or PRP + SOWPa (100 mg/kg) treatment for 72 h significantly improved the cell viability of ACL fibroblasts from 100 ± 7.5% (control) to 156.85 ± 12.82%, 188.08 ± 15.92%, and 223.67 ± 18.82%, respectively, which was evidenced by individual decreased apoptosis rate from 31.26 ± 2.35% (control) to 20.80 ± 1.89%, 18.01 ± 1.55% and 9.33 ± 0.78%. Furthermore, the motility of ACL fibroblasts was significantly improved with increased migrated cell number per field from 5 for control to 26 for PRP, 36 for SOWPa and 44 for PRP + SOWPa, respectively. Moreover, the protein expression of differentiation markers (RUNX2, ALP, BMP2 and Col I) and TLR-4 and phosphorylated p65 (p-p65) was inhibited by the above treatment. Discussion and conclusions Data suggested that the addition of SOWPa to PRP increased the regenerative ability of ACL fibroblasts by blocking the TLR-4/NF-κB pathway.